Elite army sport in Czechoslovakia 1945-1960 - Václav Pechman (Jan Długosz University in Częstochowa, 2022)
The paper explores the process of forming the system of top-level sports in the Czechoslovak armed forces during 1945-1960. Emphasis is placed on examining the postwar development of the institutional framework and the impact of sociopolitical developments on the subject matter. The army's support for the training of top-level athletes was a logical consequence of the conditions existing during that period and the adoption of the model practiced in the Soviet Union and in all countries of the Eastern Bloc. After the Communist Party took power in February 1948, the new government redefined the significance of physical education and sports. Sports at the top and lower levels were stripped of their apolitical nature and inherent purposes, as the prospects of achieving top-level performances presented a potential for using the achievements for propaganda purposes by the communist regime. Amid the militant atmosphere of the Cold War, the Ministry of National Defense had a unique status, which facilitated the functioning of a government-controlled system of top-level sports training. The ministry had strong financial resources, and its sports program encompassed both professional soldiers and conscripts fulfilling their two-year military duty. On the one hand, universal conscription facilitated the identification of high-potential individuals, and on the other hand, material support and technical resources offered conditions unrivalled elsewhere. Moreover, the military environment did not contravene amateur regulations in effect at that time, and a person's military status did not contradict his or her civilian ideological principles. Following a period of searching for the optimal structural framework, an organizational structure was established that relied on Dukla Military Sports Clubs, which formed the base of world-class national teams for several subsequent generations.